Pengajaran Bahasa Inggris Interaktif Bagi Guru PAUD Di Majene - Azizah Amal; Muhammad Akil Musi; Muhammad Yusri Bachtiar; Herlina Herlina (KARYA: Journal of Educational Community Service, 2023)
The aim of this PPM activity is to help PAUD teachers in Majene Regency to find, create and apply material for English teaching and learning activities interactively and according to the children's ages. This activity was carried out in Majene Regency in order to help kindergarten teachers in Majene Regency to find and know how to actively teach English to children so that children can know and recognize vocabulary in English according to their developmental stages. Teachers as educators in early childhood education institutions play a role that is no less important than parents and the community. Education services in schools as the first and foremost place of education in early childhood education are responsible for meeting the needs of children to grow and develop. So whatever the teacher does in the school environment will have an impact on the child's life in the future. If teachers are able to provide good educational services, then children will naturally receive good learning intake too, and vice versa. The method for implementing this activity is intensive training with a combination of theory and practice as well as discussion and performance of workshop results at the end of the training. The introduction and strengthening of TEYL principles is carried out while still considering and respecting their (participants') position as teachers who have different backgrounds and experiences. This PPM activity emphasizes the use of songs, stories, games and crafts to help organize the English language learning process in PAUD.